Pengaruh sarana prasarana terhadap efektivitas proses pembelajaran di SDN 1 Maparah Ciamis - Try Riduwan Santoso; Dena Putri (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This study aims to find out how the infrastructure of the effectiveness of the learning process at SDN 1 Maparah, Panjalu District, Ciamis Regency, knowing the effect of infrastructure on the effectiveness of the learning process at SDN 1 Maparah, Panjalu District, Ciamis Regency. Infrastructure facilities include all equipment and equipment that are directly used and support in the learning process. Learning facilities are needed to support the learning process so that students more easily receive explanations from the teacher. The more complete and adequate learning facilities owned by the school will make it easier for teachers to carry out their duties as education staff. The method used in this study is descriptive method through a quantitative approach. Data collection techniques carried out by using observation, depth interview, and questionnaires. The results of the analysis is that the correlation coefficient between variable X and variable Y is 0.35. So it is in sufficient classification because it is located at intervals of 0.41-0.60, the result of significance test is 0.05 and (dk = 34-2 = 32) is obtained t table 2, 0315. Thus tcount 4.13 ≥ ttable 2.0315. So the Alternative Hypothesis (Ha) is accepted, while the Zero Hypothesis (H0) is rejected. This means that the infrastructure has an influence on the effectiveness of the learning process at SD 1 Maparah, Panjalu District, Ciamis Regency on 35 %. Those are learning room, reading book and resource, learning media, Library, laboratory, and sport facility.